Eksplorasi Teknologi 21 dalam Pengembangan Sistem Informasi Terpadu untuk Bisnis Modern - Junita Sastri (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
In the digital era of the 21st century, technology continues to develop rapidly, influencing various aspects of life, including business operations. This journal explores the concept of Technology 21 and its application in the development of integrated information systems for modern business. This research aims to understand how technological innovations, such as artificial intelligence, Internet of Things (IoT), and big data, can be integrated in information systems to increase operational efficiency and effectiveness. Through analysis of various case studies, this journal shows that integrated information systems utilizing Technology 21 not only facilitate better decision making, but also improve collaboration between departments and provide competitive advantages. By presenting the main components of an integrated information system, such as hardware, software, data, procedures, and user roles, this journal provides a comprehensive overview of the challenges and opportunities faced by businesses in adopting the latest technology. It is hoped that the findings of this research can become a reference for practitioners and researchers in understanding the importance of technology integration in information management in the modern era.